Guidelines for Art Learning Management Based on Loose Parts Concept to Promote Creative Thinking Skills for Early Childhood - chaiopanon, Jantana; Boonyananta, Soamshine (SSRU Academic Journal of Education, 2024)
The purpose of this research was 1) to study the opinions of experts towards the art learning management approach based on the Loose Parts Concept; and 2) to develop an art learning management approach based on the Loose Parts concept to promote creative thinking skills for early childhood. The sample group in this research consisted of 9 art activity management experts. The research tool was an interview form for art activity management experts. to promote creative thinking skills for early childhood the interview topics consisted of 1) Organizing art activities to promote creative thinking skills, 2) Guidelines for setting objectives, 3) Appropriate nature of learning activities, 4) Learning media used in organizing activities, and 5) measurement and evaluation. The results of the research found that 1) Experts are of the opinion that art learning management based on the concept of Loose Parts Activities must be organized to have a variety of learning through hands-on activities. From materials and equipment that are diverse in size, color, and texture, insert problems for children to develop thinking processes, experiment and solve problems on their own. 2) Guidelines for art learning management according to the Loose Parts Concept to promote creative thinking skills for early childhood children, consisting of (1) Environment Management (2) Children Participate in Planning (3) Good Media Arts, and (4) Roles of Teachers and Parents.